Instability of Vertical Constant Through Flows in Binary Mixtures in Porous Media with Large Pores. (12th February 2019) - Capone, Florinda; De Luca, Roberta; Torcicollo, Isabella
Abstract : A binary mixture saturating a horizontal porous layer, with large pores and uniformly heated from below, is considered. The instability of a vertical fluid motion (throughflow) when the layer is salted by one salt (either from above or from below) is analyzed. Ultimately boundedness of solutions is proved, via the existence of positively invariant and attractive sets (i.e. absorbing sets). The critical Rayleigh numbers at which steady or oscillatory instability occurs are recovered. Sufficient conditions guaranteeing that a secondary steady motion or a secondary oscillatory motion can be observed after the loss of stability are found. When the layer is salted from above, a condition guaranteeing the occurrence of "cold" instability is determined. Finally, the influence of the velocity module on the increasing/decreasing of the instability thresholds is investigated.